Assessing the understanding and practice of fardhu prayer among PKT students: a survey-based analysis - Aiezzatul Akmaliyah Binti Abdullah; Zainun Binti Salleh; Salmi Binti Mohd (Lentera Negeri, 2024)
Prayer functions as the pillar of religion and the main axis of a believer's faith. This study examines the implementation of obligatory prayer practices and the identification of Prayer Pillars among PKT students. This is because various parties, particularly Islamic Studies lecturers, often raise concerns about students' involvement in prayer in terms of practice and knowledge of Prayer Pillars. Although it is not a new issue, it still needs to be emphasized for the well-being of the Muslim community. A total of 30 students were selected to participate in this study as respondents. This research study used a questionnaire survey method. Through the distribution of questionnaires, the study found that almost students did not perform prayer perfectly, especially in terms of recitation during prayer and inability to identify the Prayer Pillars. This matter needs to be taken seriously by all parties to ensure the implementation of obligatory prayer in students' daily routines. It is anticipated that through the discoveries of this investigation and multiple suggested courses of action, there may be an enhancement in the extent of mandatory prayer engagement and the recognition of Prayer Pillars within the student population.